(untitled) (Revista Internacional de Folkcomunicação, 2020)
The importance of having a specific teaching material for the quilombola community is understood, so that students can learn about the culture of their community and have a meaningful learning, for those who do not belong to the traditional community, they can know the people life style and so respect them. The study is descriptive with a qualitative approach and aims to analyze the teaching material “Quilombolas Narratives: dialogue - know - communicate”, carried out by the São Paulo State Department of Education and by the Educational Inclusion Center, recognizing the importance of narratives as an instrument of knowledge and appreciation of the quilombos traditions, stories, struggles and resistance, as a didactic resource, they allow textual, grammatical and sociocultural exploration, providing interdisciplinarity and interaction with traditional knowledge. Quilombola; Education; Afro-Brazilian community; Traditional people.